Surgical antimicrobial prophylaxis among surgical patients: results from a retrospective observational study at a public hospital in Liberia - Michelle Niescierenko; John Shakpeh; Kayla Enriquez; Saned Raouf; Finda Mayah-Toto (BMJ Open)
Background Surgical antibiotic prophylaxis (SAP) is one of the most effective measures to prevent surgical site infections (SSIs). According to WHO SAP guidelines, SAP requires appropriate indication for administration and delivery of the antimicrobial agent to the operative site through intravenous administration within 60–120 min before the initial surgical incision is made. In Liberia, it is unknown how surgeons practice and there has been anecdotal observation of antibiotic overuse.Objective To elucidate baseline SAP compliance, particularly appropriate SAP use based on wound class and time of antibiotic administration.Methods An observational, cross-sectional study was conducted from November to December 2017. One-day training was provided on SAP/SSI to 24 health workers by the Ministry of Health and WHO. Following this training, surgical cases (general surgery and obstetrics and gynaecology (OB/GYN) underwent chart review with focus on time of SAP administration and appropriate SAP based on Centers for Disease Control and Prevention (CDC) wound classification.Results A total of 143 charts were reviewed. Twenty-nine (20.3%) cases showed appropriate prophylaxis through administrations of antibiotics 120 min before surgical incision, resulting in SAP compliance. One hundred and fourteen cases (79.7%) showed SAP noncompliance with timing of antibiotic administration. Of the OB/Gyn cases, 109 wounds were classified as Class I (clean) and one wound was classified as Class III (contaminated). For General Surgical cases, 32 wounds were classified as Class I and one as Class III. Of the 109 Class I OB/Gyn surgeries, 24 (22%) were appropriately given antibiotics based on the CDC wound guidelines while 78% were non-compliant with recommendations. Of the 32 Class I General surgery cases, 4 (12.5%) were compliant with antibiotics guidelines while 28 (87.5%) were not.Conclusion Compliance with SAP is low. More studies need to be done to explore the contributing factors to this. Implementing mechanisms to achieve proper use of SAP is needed.